2022
DOI: 10.1186/s12909-022-03567-5
|View full text |Cite
|
Sign up to set email alerts
|

Training of radiotherapy professionals: status, content, satisfaction and improvement suggestions in the Greater Region

Abstract: Background The initial training of Radiation Oncology professionals can vary widely across Europe. The aim of this study was to assess the status and content of the initial training programs currently implemented in the Greater Region: Lorraine (Nancy, France), Saarland (Homburg, Germany), Luxembourg, and Liège (Wallonia, Belgium). Methods A survey was developed to investigate (1) the overall satisfaction, learning objectives, and teaching methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Questionnaire-based studies often face discreet participation due to addressing difficulties and professionals' lack of availability amid their routine challenges. A European survey that evaluated the satisfaction of radiotherapy professionals in relation to their training reached an audience of 38 professionals working in France, Germany and Belgium [9] . In other words, the scope of the sample detailed here was quite reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaire-based studies often face discreet participation due to addressing difficulties and professionals' lack of availability amid their routine challenges. A European survey that evaluated the satisfaction of radiotherapy professionals in relation to their training reached an audience of 38 professionals working in France, Germany and Belgium [9] . In other words, the scope of the sample detailed here was quite reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Dubonis and colleagues published the results of a survey with 38 radiotherapy professionals (including doctors, physicists, and technicians) working in France, Germany, and Belgium, highlighting a significant lack in the practical aspect of training. Only a fifth of the respondents felt that their training was adequate when they entered the job market [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Simulation-based training, rooted in active learning theories from cognitive and learning sciences, is increasingly sought after in modern medical education across various specialties [ 38 ]. In the field of radiation oncology, there is a significant demand for more practical lessons in training healthcare professionals [ 39 ]. However, despite their didactic advantages, the adoption of simulation-based teaching concepts in radiation oncology has been limited, possibly due to the associated requirements for personnel, time, and financial resources.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that there is a great demand for more practical lessons in the training of radiation oncology professionals [ 33 ]. While it has been demonstrated that simulation-based education has a high benefit in radiation oncology, it mainly addresses the teaching of contouring.…”
Section: Discussionmentioning
confidence: 99%